Термодинамические исследования системы CaCl₂ – MgO - Гринь, Григорий Иванович; Дейнека, Дмитрий Николаевич; Козуб, П. А.; Лавренко, Антонина Александровна; Бондаренко, Людмила Николаевна (НТУ "ХПИ", 2006)
In the paper the system СаCl₂ – MgО is studied, the thermodynamic calculation of possible reactions taking into account the magnesium and calcium compounds is fulfilled at the temperature interval 298–1200 K. It is proved that using the magnesium chloride or calcium chloride as solutions for mass preparation the adsorbent composition will be the same. It as determined that the magnesium oxide presence in the adsorbent promotes resistance at the drying and deposition
Keywords: металлы платиновой группы; азотная кислота; адсорбент; растворы